Outcomes following Aggressive Surgical Resection of Intra-Medullary Spinal Cord Tumours with Intra-Operative Neuro-Monitoring - Rajendra Tiruchelvarayan MBBS, FRCS (Neurosurgery) (Ireland); Man Hon Tang MBBS; Sanjaya Perera MBBS, MRCS; Yew Long Lo MBBS, MMed (Internal Medicine), FAMS (Proceedings of Singapore Healthcare, 2013)
Introduction: Intra-medullary spinal cord tumours (IMCST) are relatively uncommon tumours of the central nervous system which can result in severe neurological disorder if untreated. Histologically, IMCSTs are often either biopsied or excised subtotal, but this may lead to early tumour recurrence and progressive neurological impairment. In an attempt to improve outcomes, the recent trend is to perform more radical tumour resection guided by intra-operative monitoring (IOM). However, there are no controlled studies comparing the resection of IMCSTs with or without IOM. In this single surgeon series, we analyse outcomes following optimal resection of IMCSTs in conjunction with IOM. Methods: In this retrospective single surgeon series, case notes and history of patients who underwent surgery between 2006–2012 at the Singapore General Hospital's Neurosurgery Department, were studied. IOM with somatosensory evoked potential (SSEP) and motor evoked potential (MEP) were utilised to facilitate optimal tumour resection. Neurological status were compared pre- and post-operatively with long-term follow-up on outcomes. Magnetic resonance imaging was used pre- and post-operatively to assess the degree of tumour resection. Results: Thirteen consecutive patients with IMCSTs (five males, mean age 36 years, range 12–60) underwent surgical treatment and were included in this study. Radical surgical resection was performed for 11 patients, while the remaining two had biopsies and partial debulking as frozen section showed high grade astrocytomas. Histology revealed six cases of ependymoma, five cases of astrocytoma, and one of hemangioblastoma and neuroenteric cyst. There was one case of wound infection which was treated successfully. There were no cases of cerebrospinal fluid leakage. Two patients had pre-existing spinal deformity, and underwent posterior instrumented fusion concomitantly. The neurological state improved or remained stable in 11 (85%) patients, and two patients had immediate post-operative neurological deterioration which improved subsequently with physiotherapy over one to two months. Favourable functional outcomes were observed in the majority of patients during follow-up. The patients with high grade tumours were treated with adjuvant radiotherapy post-operatively, however, they showed a poorer long-term outcome. The mean follow-up was 3.2 years from operation. Conclusion: Radical resection of intra-medullary tumours with IOM leads to a favourable functional outcome in selected groups of patients.